2014
DOI: 10.4103/2230-8210.145074
|View full text |Cite
|
Sign up to set email alerts
|

Twins and endocrinology

Abstract: Twins are two independent babies delivered during the same pregnancy and are divided as monozygotic or dizygotic based on their origin. Dizygotic twins are similar to two siblings and have different genetic information. In contrary, monozygotic twins have a similar genetic identity and provide a unique opportunity to evaluate the contribution of genetic and environmental factors of the disease. The endocrine and metabolic disorders affect a large number of the population including the twins. Diabetes, obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The genetic basis for developing T2DM has been recognized for a long time. The concordance of T2DM in monozygotic twins is ~70.0% compared with 20.0-30.0% in dizygotic twins and a sibling of an affected individual has about three times higher risk for developing the disorder than the general population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic basis for developing T2DM has been recognized for a long time. The concordance of T2DM in monozygotic twins is ~70.0% compared with 20.0-30.0% in dizygotic twins and a sibling of an affected individual has about three times higher risk for developing the disorder than the general population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of HT and the production of these self-antibodies is still unclear but several genetic factors, environmental factors, and epigenetic factors may play a role [11]. A study conducted by Brix et al showed when comparing monozygotic twins and dizygotic twins, monozygotic twins had a higher concordance rate of HT (50% vs 0 %) and autoantibodies (80% vs 40%) [7,12]. When examining specific alleles, a case-control study showed having HLA-B*46:01 was associated with HT [13].…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…Another study revealed that the prevalence of HT ranged from 4.8-25.8% in women and 0.9-7.9% in men, confirming that HT is more common in women than men [6]. When comparing the concordance rate for monozygotic twins as compared with dizygotic twins, monozygotic had a high rate of 55% vs 0% of the dizygotic twins [7]. With respect to race, Caucasians have the highest rate of developing HT, with a total incidence rate of 5% [8].…”
Section: Introductionmentioning
confidence: 96%
“…[5][6][7] Due to the young age of T1D onset and lower familial clustering than type 2 diabetes, pathogenesis other than gene should be considered in T1D. 8 As known, maternal immune or cytokine changes can be transferred to the fetus through the placenta, thereby affecting fetal development. [9][10][11] Thus, maternal immune related diseases could be important in the cause of T1D.…”
Section: Introductionmentioning
confidence: 99%